Pengaruh Ekstraksi Benih dengan HCl dan Jenis Wadah Penyimpanan terhadap Daya Simpan Benih Tomat (Lycopersicum esculentum Mill.) - Maheswari, Mea Aprilia; Astawa, I Nyoman Gede; Darmawati, Ida Ayu Putri (Agrotrop : Journal on Agriculture Science, 2024)
Effect of Seeds Extraction with HCl and Types of Storage Packaging on Storability of Tomato Seeds ( Lycopersicum esculentum Mill.) . This study aims to determine the effect of seeds extraction with HCl and types of storage packaging on storability of tomato seeds ( Lycopersicum esculentum Mill.). This study used a factorial Completely Randomized Design with two factors. The first factor was HCl extraction which consists of five levels, namely HCl concentration 0% (K 0 ), 1% (K 1 ), 2% (K 2 ), 3% (K 3 ) and 4% (K 4 ). The second factor was the type of storage packaging which consists of three levels, namely aluminium foil (J A ), plastic clip (J P ) and glass bottles (J B ). Each treatment was repeated 3 times. The research was conducted at the Plant Breeding and Seed Technology Laboratory, Faculty of Agriculture, Udayana University from September-December 2022. The result showed the storage for 12 weeks used HCl extraction 2% in aluminium foil (K 2 J A ) obtained the best average value to maintain the storabilitu of tomato seeds which is indicated by the value of water content (5,04%), germination (86,66%), simultaneous growth (82,22%) and vigor storability (82,22%) compared to another HCl concentration and storage packaging.